Efficacy of a Synergistic Blend of Organic Acids and ß-1,4 Mannobiose on Cecal Salmonella Counts and Growth Performance in Salmonella Challenged Broiler Chickens: A Meta-Analysis - Sandra J. A. van Kuijk; Yanming Han (Animals, 2021)
This study aimed at investigating the effect of a functional synergistic feed additive blend, containing organic acids and ß-1,4 mannobiose, on cecal Salmonella counts and growth performance of broiler chickens. A meta-analysis combining 13 individual studies, executed in Salmonella-challenged broilers comparing a control diet with and without the synergistic blend, was performed. Cecal Salmonella colonies and overall growth performance were measured. Raw data from all studies were combined and analyzed using PROC MIXED in SAS, taking the within and between-study variation into account. In the first 14 days post-inoculation (DPI), cecal Salmonella was reduced by 0.429 log CFU/g (p = 0.011, n = 10 comparisons from five studies) when feeding the synergistic blend compared to the control group. During 15–34 DPI, the overall means were not different between treatments (0.069 log CFU/g; p = 0.519, n = 12 comparisons from eight studies). The feed conversion ratio was improved when feeding the synergistic blend compared to the control diet (1.474 vs. 1.482, respectively; p = 0.002). In conclusion, feeding a synergistic blend, containing organic acids and ß-1,4 mannobiose amongst other ingredients, reduced cecal Salmonella counts during the first 14 DPI and improved growth performance of Salmonella challenged broilers compared to a control diet.